Presynaptic Calmodulin targets: lessons from structural proteomics. (4th March 2017) - Lipstein, Noa; Göth, Melanie; Piotrowski, Christine; Pagel, Kevin; Sinz, Andrea; Jahn, Olaf
ABSTRACT: Introduction : Calmodulin (CaM) is a highly conserved Ca 2+ -binding protein that is exceptionally abundant in the brain. In the presynaptic compartment of neurons, CaM transduces changes in Ca 2+ concentration into the regulation of synaptic transmission dynamics. Areas covered : We review selected literature including published CaM interactor screens and outline established and candidate presynaptic CaM targets. We present a workflow of biochemical and structural proteomic methods that were used to identify and characterize the interactions between CaM and Munc13 proteins. Finally, we outline the potential of ion mobility-mass spectrometry (IM-MS) for conformational screening and of protein-protein cross-linking for the structural characterization of CaM complexes. Expert commentary : Cross-linking/MS and native MS can be applied with considerable throughput to protein mixtures under near-physiological conditions, and thus effectively complement high-resolution structural biology techniques. Experimental distance constraints are applicable best when obtained by combining different cross-linking strategies, i.e. by using cross-linkers with different spacer length and reactivity, and by using the incorporation of unnatural photo-reactive amino acids. Insights from structural proteomics can be used to generate CaM-insensitive mutants of CaM targets for functional studies in vitro or ideally in vivo .